Shodaqah Sebagai Metode Pendidikan Memasyarakatkan Ekonomi Syariah - Hidayat Hidayat (Jurnal Budi Pekerti Agama Islam, 2024)
Economic problems that occur such as multidimensional poverty in the form of education, social, health and politics. One ethod of improving the economy and poverty problems is through grounding the Islamic economy with the alms instrument. The purpose of this study is to examine the grounding of the sharia economy through the alms instrument to improve the welfare of the community through the alms instrument. This study uses a literature review that contains theories, findings and materials from previous studies as the basis for writing this article. The results of the study show that grounding the Islamic economy to the community is not only by increasing the number of Islamic financial institutions, but rather to the implications of Islamic values such as the practice of alms. Through almsgiving, Allah swt will be able to cover the needs of the poor and the giver of alms will be doubled according to His promise.